Myasthenic syndrome: effect of choline, plasmapheresis and tests for circulating factor. - Kranz, H (1980)
In a patient with myasthenic syndrome neuro-muscular transmission was characterised by depression and facilitation. The relative extent of these two processes varied between muscles, and in the one muscle with time. Guanidine HCl treatment corrected the electrophysiological defect. Oral choline increased muscle action potential amplitude in response to single shocks. Intravenous choline produced features indicating cholinergic autonomic stimulation. Pimozide and plasmapheresis had no effect. Animal in-vivo and in-vitro studies performed to detect a circulating factor which interferes with neuro-muscular transmission were negative.